Fluoride effects on leaves of aquatic Salvinia auriculata - Peixoto, Paulo Henrique Pereira; Pimenta, Daniel Sales; Antunes, Flávia (Pesquisa Agropecuaria Brasileira, 2005)
<!--[if gte mso 9]> Normal 0 <![endif]--> <!-- /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal {mso-style-parent:""; margin:0cm; margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:10.0pt; font-family:"Times New Roman"; mso-fareast-font-family:"Times New Roman"; mso-ansi-language:PT-BR;} @page Section1 {size:612.0pt 792.0pt; margin:70.85pt 3.0cm 70.85pt 3.0cm; mso-header-margin:36.0pt; mso-footer-margin:36.0pt; mso-paper-source:0;} div.Section1 {page:Section1;} --> The objective of this work was to evaluate the effects of fluoride on leaves of aquatic Salvinia auriculata Aubl., to supply subsidies for the use of this species as an environmental pollution bioindicator. The plants were cultivated under controlled conditions in pots containing nutritive solutions, and were submitted to simulated rain containing KF, in concentrations of 0, 13, 26 and 39 mM, in the morning, during five consecutive days. Results evidenced the occurrence of morphological and anatomical damages involving trichome and adaxial surface of the leaf necrosis. Alterations in the activity of peroxidase, polyphenoloxidase, superoxide dismutase, and catalase enzymes indicated the occurrence of oxidative damages in response to fluoride, although lipid peroxidation tests showed negative results. Alterations in pigment concentration also pointed to the occurrence of oxidative stress, caused by fluoride present in the simulated rain. The morphological, anatomical, enzymatic, and pigment composition alterations in S. auriculata can be used in atmospheric pollution biomonitoring, because they are easy to detect through simple methodologies.